Quantitative LC-MS proteoform profiling of intact wheat glutenin subunits. (July 2020) - Bacala, Ray; Fu, Bin Xiao; Perreault, Hélène; Hatcher, Dave W.
Abstract: Methodology for the quantitative analysis of intact glutenin proteins by ESI-LC-MS was developed with 1 Da mass resolution, constituting the first published application of proteoform profiling to plant biology. Two parent lines and 28 F5 crosses were analyzed in two blocks, 14 months apart. Control sample data were used to align retention times and normalize abundance between sample sets. A total of 4622 observations of 347 distinct proteoforms between 17 899 and 88 744 Da were observed. Proteoform abundances spanned a 1000-fold range and were linear (r 2  > 0.990) with dilution. A novel method for the objective elimination of low intensity, noise-dominated data using replicate variability within the dataset is presented. Two abundant PTMs were detected; one known but uncharacterized Bx and Dy high-molecular-weight glutenin subunit (HMWGS) PTM and the other in 24 low molecular weight proteoform pairs. Finally, 16 abundant proteoforms were detected in progeny but not in either parent. This application should increase the statistical power of correlations between gluten complement and functional data and drive the detection of novel PTMs that may indicate differential regulation of the cellular processes related to quality. Graphical abstract: Image 1 Highlights: Quantitative ESI-LC-MS proteoform profiling was performed on wheat glutenin extracts. Inter-day retention time and MS sensitivity drift were corrected using control sample data and custom processing scripts. Proteoform response (abundance) linearity was established using a control sample dilution series. Analysis of two parents and 28 crosses revealed several proteoforms not present in either parent. Two previously uncharacterized HMWGS and LMWGS post-translational modifications were detected.